Cytomegalovirus Infection in an Adult Patient With Neuromyelitis Optica and Acute Hemorrhagic Rectal Ulcer: Case Report and Literature Review - Luo, Jinmei; Shi, Xiaowei; Lin, Ying; Cheng, Na; Shi, Yunfeng; Wang, Yanhong; Wu, Ben-Quan (Frontiers in Immunology, 2020)
Background: Previous infectious or inflammatory events may be involved in the pathogenesis of neuromyelitis optica (NMO), potentially by triggering an autoimmune response. Cytomegalovirus (CMV, also termed human betaherpesvirus 5)-related NMO (CMV-NMO) is rarely reported. Acute hemorrhagic rectal ulcer (AHRU) is a rare disease with a largely unknown pathogenesis. Herein, we reported a co-NMO and AHRU case associated with CMV infection. In addition, we review previously reported cases of CMV-NMO and CMV-AHRU. Case presentation: A 40-year-old female diagnosed with aquaporin4 (AQP4)-IgG+ NMO and a poor response to high-dose intravenous methylprednisolone and immunoglobin, followed by three rounds of plasma exchange was transferred to Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, China . She developed repeated acute lower gastrointestinal hemorrhage from the third day of admission. Abdominal computed tomography angiography (CTA) and interventional angiography did not detect any bleeding vessel. Bedside colonoscopy revealed a large ulcer-like lesion at 10 cm above the anus. Rectal biopsy pathology confirmed a CMV infection on day 23 post-admission, and cerebrospinal fluid (CSF) pathogen gene sequencing detected CMV gene copies on day 25 post-admission. After 2 weeks of treatment with ganciclovir and sodium phosphinate, the patient's lower gastrointestinal bleeding stopped, and her limb muscle strength and visual acuity gradually improved. After 4 weeks of antiviral therapy, colonoscopy showed that the intestinal wall of the original lesion was smooth. Hematoxylin and eosin (HE) staining and immunohistochemistry (IHC) of a biopsy specimen was negative for CMV, her right eye vision was normal, and limb muscle strength had recovered. Serum AQP4-IgG was negative, and lesions on brain magnetic resonance imaging (MRI) manifested shrinkage. Conclusions: The benefits of antiviral therapy remain unclear; however, clinicians should be aware of the possibility of CMV-related NMO, if NMO was refractory to high-dose intravenous methylprednisolone, immunoglobin, and plasma exchange. Moreover, clinicians should consider the possibility of CMV-related AHRU when recurrent acute lower gastrointestinal bleeding occurs in a patient.